Managerial Excellence as the Basis for the Success in the Digital Transformation of Public Services - E. V. Vasil’eva (Управленческие науки, 2020)
The goal of improving the efficiency of public administration is a priority in the implementation context of the Digital Economy of the Russian Federation Program. The paper provides the formation of a strategy for managing public service personnel based on the principles of a management staff diversity and employees involvement to solve problems of increasing the level of personnel potential. The purpose of the study is to determine the requirements for public service management, to identify a new set of tasks for the top management of a company that transfers most of its activities to digital platforms. The author presents an approach to improving a company’s performance in the digitalization of economy and society. The implementation of the strategy for management excellence is based on the principle of “smart simplicity” and the formation of new professional qualities of the head of the public service. The paper gives a feature of using the 360-degree competency assessment methodology. It presents the world and domestic experience of changing the strategy of personnel management in a modern organization that has embarked on the path of digital transformation. The main requirements to the competence of the Executive who should have knowledge in professional and technical fields being able to think globally and have a wide managerial experience and vision, to have foresight being proactive to turn the company strategy into a new quality. A list of key indicators has been formulated that can be used for monitoring personnel management activities aimed at the successful implementation of a managerial excellence strategy.